Stereotactic Ablative Body Radiotherapy Versus Radical Radiotherapy: Comparing Real-World Outcomes in Stage I Lung Cancer. Issue 10 (October 2019) - Phillips, I.; Sandhu, S.; Lüchtenborg, M.; Harden, S.
Abstract: Aims: Stereotactic ablative body radiotherapy (SABR) is now considered the standard of care for medically inoperable stage I non-small cell lung cancer (NSCLC). The English National Cancer Registration and Analysis Service (NCRAS) collects data on all patients diagnosed with lung cancer, including information on treatment. We wanted to compare outcomes for patients with stage I NSCLC treated with radical radiotherapy with either SABR or fractionated radiotherapy. Materials and methods: All patients diagnosed with stage I NSCLC in 2015 and 2016 were identified from the NCRAS dataset, validated by the National Lung Cancer Audit, and their treatment data were collated. For patients who received radiotherapy, those receiving radical dose fractionations, including SABR, were identified through linkage to the national Radiotherapy Dataset. Clinical outcomes for those receiving SABR or more fractionated radical radiotherapy were compared using univariate and fully adjusted Cox proportional hazards models. Results: In total, 12 384 patients with stage I NSCLC were identified during the study period; 53.5% underwent surgical resection, 24.3% received no documented treatment, 18.6% received radical radiotherapy and 3.5% received other non-curative-intent treatments. For those receiving radical radiotherapy, 69% received SABR and 31% received fractionated treatment. The hazard ratio of death for the 1587 patients who received SABR was 0.69 (95% confidence interval 0.61–0.79) compared with 717 patients who received radical fractionated radiotherapy; this benefit was seen for both stage Ia and stage Ib disease. The median overall survival was also longer for SABR versus radical radiotherapy (715 days versus 648 days). Exploratory travel time analysis shows that compared with stage I NSCLC patients receiving SABR, those receiving fractionated radiotherapy and those receiving no active treatment would have to travel longer and further to reach their nearest radiotherapy SABR centre. Conclusion: This study adds to the data that SABR has a survival benefit when compared with fractionated radical radiotherapy. Although the use of SABR increased in England over this study period, it has still not reached levels of use seen in other countries. This study also highlights that one quarter of stage I NSCLC patients overall received no active treatment. Highlights: For stage I NSCLC patients treated with radical radiotherapy, survival is improved when SABR is used. 69% of patients in England receiving radical radiotherapy for stage 1 NSCLC receive SABR, this is lower than other countries. 24% of patients with stage I NSCLC in England receive no active treatment.